Paediatric Bronchiectasis in a Resource-Constrained Centre: A Case Series - Kuti BP; Jallow M; Jobarteh ML (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2024)
Bronchiectasis denotes fixed and often irreversible dilatation of the bronchial wall caused by persistent inflammation and infection. Children with bronchiectasis in developing countries suffer recurrent hospitalisation and poor quality of life and usually succumb to the condition. These children are poorly recognised, misdiagnosed, and under-reported. We report five cases of computerised tomography-diagnosed paediatric bronchiectasis managed at the Edward Francis Small Teaching Hospital (EFSTH), Banjul, The Gambia. The ages of the children at presentation ranged from 3 to 14 years, and they all had recurrent chest infections. Four out of the five cases had Pulmonary Tuberculosis, among whom two cases had HIV/TB co-infections, and the only non-TB, non-HIV case had features of Down syndrome with congenital heart lesions. All the cases had growth impairment; digital clubbing was observed in four, and low peripheral oxygen saturation in room air in three of the five children. These cases are reported to increase the index of suspicion among clinicians working in resource-limited settings to consider the diagnosis of bronchiectasis in children with recurrent chest infections. Early diagnosis and prompt management, including appropriate follow-up care, will improve the quality of life of these children and ensure better management outcomes.